The Content of Chemical Elements in the Organism of Anura, Amphibia, as an Indicator of the Environmental Conditions; Russian Journal of Herpetology; Vol. 12, N Supplement - Kuranova V. N. (2005, 2005)
В фонде НТБ ТПУ отсутствует